The impact of foreign direct investment on agricultural output of Nigeria - Yusuf, Kabir Usman (2015)
This study examines the impact of Foreign Direct Investment on Agricultural output in Nigeria from 1970-2012 using an autoregressive distributed lag (ARDL) model. Data were sourced from the National Bureau of statistic (NBS), Central Bank of Nigeria (CBN), and the World Development Indicators. Results from the analysis reveal that Foreign Direct Investment, Government expenditure and Exchange rates in the period under study have significant positive effects on Agricultural output, whereas Interest rates and Inflation variables have negative effect on Agricultural output, although the Inflation rate is not significant. Increase in volume of Foreign Direct Investment is recommended, Government and other stakeholders should seek Foreign Direct Investment. It is also recommended to improve macroeconomic policies that will encourage agricultural sector productivity in Nigeria